Warhol after Warhol : secrets, lies, & corruption in the art world - Dorment, Richard (Pegasus Books, 2023)
A story spanning a decade and starring a cast of characters straight out of novel-from rock icons and film stars, art dealers and art forgers-brings to life the bitter debate over the authenticity of a series of paintings by the most famous American artist of the 20th century.